1,3-Dimethyl-3-tetradecyl-1H-1,5-benzodiazepine-2,4(3H,5H)-dione - Dardouri, Rachid (International Union of Crystallography, 2011)
The seven-membered ring of the title compound, C(25)H(40)N(2)O(2), adopts a boat-shaped conformation (with the C atoms of the fused-ring as the stern and the methine C atom as the prow). The tetradecyl substituent occupies an equatorial position, with the tetradodecyl chain exhibibiting an an all-trans conformation.